2010
DOI: 10.2147/opth.s11762
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal visual evoked potentials in amblyopia due to anisometropia

Abstract: Purpose:To investigate multifocal visual evoked potentials (mfVEP) of the amblyopic and fellow eye in amblyopia due to anisometropia.Methods:We recorded mfVEP in both eyes of 15 anisometropic amblyopic patients and 15 normal control subjects. The responses from the central 7.0° arc of the visual field were measured, and changes in latency and amplitude were compared between the amblyopic, fellow, and normal control eyes.Results:There was a significant difference in the latency and amplitude of mfVEP between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Our results, demonstrating that the sensitivity of the ERPs for detecting amblyopic effects at the might depend on adequate stimulus scaling, may help to reconcile the divergent VEP results concerning the presence or absence of the amblyopic deficit outside the fovea. 11,[13][14][15][17][18][19] They are also in agreement with previous observations that magnification scaling is a highly important variable that influences the elicited pattern evoked potential. 13 Our findings also closely parallel the psychophysical results of Katz and colleagues, 2 who showed that peak contrast sensitivity of amblyopic eyes at the periphery benefitted more from an increase in stimulus size, reaching the sensitivity of the fellow eyes for large central stimuli.…”
Section: Importance Of Cortical Magnificationsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results, demonstrating that the sensitivity of the ERPs for detecting amblyopic effects at the might depend on adequate stimulus scaling, may help to reconcile the divergent VEP results concerning the presence or absence of the amblyopic deficit outside the fovea. 11,[13][14][15][17][18][19] They are also in agreement with previous observations that magnification scaling is a highly important variable that influences the elicited pattern evoked potential. 13 Our findings also closely parallel the psychophysical results of Katz and colleagues, 2 who showed that peak contrast sensitivity of amblyopic eyes at the periphery benefitted more from an increase in stimulus size, reaching the sensitivity of the fellow eyes for large central stimuli.…”
Section: Importance Of Cortical Magnificationsupporting
confidence: 91%
“…These studies, on the other hand, tend to find amplitude and latency differences at the perifoveal region as well as at the fovea, even though they are smaller in size. [17][18][19] A few issues, if considered, might help to reconcile the different conclusions of these studies. One is the effect of decreased acuity on the event-related potentials (ERPs).…”
mentioning
confidence: 99%
“…In a study evaluating the multifocal VEP test results of amblyopic patients, it has been reported that VEP latency was longer and amplitude was lower in amblyopic eyes. 20 Our findings that amblyopic eyes had prolonged pupil contraction latency, or in other words, showed a longer delay between light stimulus and pupil contraction compared to healthy fellow eyes supports the view that afferent transmission is slowed in amblyopia. Dynamic pupillometry enables the objective and reliable recording of pupillary light reflex responses and independent evaluation of several parameters that reflect pupil movements.…”
Section: Discussionsupporting
confidence: 79%
“…17,18,19 Longer latencies and lower amplitudes in visual-evoked potential (VEP) and markedly reduced responses in pattern electroretinography have been documented in electrophysiological tests of amblyopic eyes. 20,21 Considering the possibility that retinal ganglion cells and anterior visual pathways may be affected in amblyopic eyes, studies have also been conducted to evaluate pupillary light reflexes. Measurements with neutral density filters have revealed relative afferent pupillary defect in amblyopic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that the monocular and binocular deficits in amblyopia are associated with an active suppression of inputs from the amblyopic eye within the visual cortex. 5-8 For example, a number of neurophysiological 9 and neuroimaging studies 10-12 have demonstrated that amblyopic eye viewing generates significantly less cortical activation in the visual cortex than fellow eye viewing. This is consistent with active suppression or inhibition of neural function, 13 which has been linked to GABAergic neural circuitry.…”
Section: Introductionmentioning
confidence: 99%